Synthesis and Properties of Octet NiCr Alloy Lattices Obtained by the Pack Cementation Process - Peng Zhao; Deqing Huang; Hongmei Zhang; Weiwei Chen; Yongfu Zhang (Applied Sciences, 2023)
NiCr alloys with different components were obtained by pack chromation and homogenization heat treatment of octet Ni lattice. The microstructure, alloy composition, microhardness and quasi-static compression properties of the NiCr lattice were tested. The results showed that after homogenization heat treatment, the NiCr alloy lattice had an austenitic structure with uniform composition. Compared with the pure nickel lattice, the microhardness, compressive strength, elastic modulus and energy absorption of the NiCr lattice increased with the increase of chromium content. The microhardness, specific strength, specific modulus and specific energy absorption of the Ni-45Cr alloy were 363 HV, 11.1 MP/(g/cm3), 1169.1 MP/(g/cm3) and 10 J/g, respectively, which were attributed to the solid solution strengthening provided by chromium and the increase in density. NiCr alloy lattices have high strength and toughness and may have potential applications in high-temperature filters or heat exchangers.